2014
DOI: 10.1093/jnci/dju092
|View full text |Cite
|
Sign up to set email alerts
|

Benefits, Harms, and Costs for Breast Cancer Screening After US Implementation of Digital Mammography

Abstract: The transition to digital breast cancer screening in the United States increased total costs for small added health benefits. The value of digital mammography screening among women aged 40 to 49 years depends on women's preferences regarding false positives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 124 publications
(108 citation statements)
references
References 39 publications
1
101
0
2
Order By: Relevance
“…[60][61][62] Based upon modelling of a transition from film to alldigital screening in the USA, Stout et al 63 estimate that digital screening contributes an additional 220 FPs per 1000 females above the FP incidence seen with the current mixed use of film and digital. It can be suggested that the rise in the FP rate following the transition to digital technology is actually associated with the use of computer-aided detection (CAD) image interpretation software rather than being attributed to factors inherent to the acquisition of images by digital mammographic units themselves.…”
Section: Screening Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…[60][61][62] Based upon modelling of a transition from film to alldigital screening in the USA, Stout et al 63 estimate that digital screening contributes an additional 220 FPs per 1000 females above the FP incidence seen with the current mixed use of film and digital. It can be suggested that the rise in the FP rate following the transition to digital technology is actually associated with the use of computer-aided detection (CAD) image interpretation software rather than being attributed to factors inherent to the acquisition of images by digital mammographic units themselves.…”
Section: Screening Protocolmentioning
confidence: 99%
“…From a financial perspective, diagnostic follow-ups are estimated to cost anywhere from $134.80 USD for additional imaging to $1374.69 USD for invasive diagnostic testing per FP. 63 Although these harms are predominantly short term and are justified for patients in which progressive invasive cancer is detected, they are considered unjustified for those patients possessing true benign cases. Benign cases are defined as cases which do not require any intervention, nor are they any cause for concern.…”
Section: Risk-benefit Analysis Diagnostic Follow-upmentioning
confidence: 99%
“…3 The number of consultations after recall in the presence of screening is calculated by using the number of screen-detected cancers and a positive predictive value (PPV) of 30% 30 (ages 50-74) or 12% (ages [40][41][42][43][44][45][46][47][48][49]. The number of consultations after recall in the absence of screening is calculated by using the number of clinically detected cancers and a PPV of 58.3%.…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Therefore, the adoption of digital mammography is likely driven primarily by something other than guidelines and has been attributed to the results of a clinical trial reports that showed superior sensitivity in digital mammography. 57 Recent analyses suggest that the small life expectancy increases may not warrant the higher costs and lower specificity of digital mammography. 57,58 Although the data do not show a costeffectiveness argument for transitioning to digital mammography, practical concerns may have driven the widespread shift observed in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…57 Recent analyses suggest that the small life expectancy increases may not warrant the higher costs and lower specificity of digital mammography. 57,58 Although the data do not show a costeffectiveness argument for transitioning to digital mammography, practical concerns may have driven the widespread shift observed in our analysis. For example, the labor-intensive process of generating and storing a film mammography and the elongated processing time play a significant role in patient throughput and the time to diagnosis.…”
Section: Discussionmentioning
confidence: 99%